Fusion of stereo vision and Time-Of-Flight imaging for improved 3D estimation. (20th November 2008) - Gudmundsson, Sigurjon Arni; Aanaes, Henrik; Larsen, Rasmus
This paper suggests an approach in fusing two 3D estimation techniques: stereo vision and Time-Of-Flight (TOF) imaging. By mapping the TOF-depth measurements to stereo disparities, the correspondence between the images from a fast TOF-camera and standard high resolution camera pair are found, so the TOF depth measurements can be linked to the image pairs. In the same framework, a method is developed to initialise and constrain a hierarchical stereo matching algorithm. It is shown that in this way, higher spatial resolution is obtained than by only using the TOF camera and higher quality dense stereo disparity maps are the results of this data fusion.